Bringing back the issues: Nigeria's Afrocentric policy under President Olusegun Obasanjo. Issue 3 (3rd July 2019) - Oshewolo, Segun
ABSTRACT: This article analyses President Obasanjo's pursuit of Nigeria's Afrocentric policy. While the general impression has been that Nigeria's Afrocentric policy succeeded under the civilian administration of Obasanjo, this study contends that the record of performance is mixed. The administration's diplomatic engagements in Africa produced a number of key upturns such as the deepening of democracy, peace and stability, and development through the framework of NEPAD. On the other hand, there were also major diplomatic setbacks. The study provides explanations for the mixed outcomes to draw important lessons that could aid the design of the policy in the post-Obasanjo era.